2022
DOI: 10.3389/fpubh.2022.944742
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and SMEs Performance Decline: The Mediating Role of Management Innovation and Organizational Resilience

Abstract: It is a major practical problem to find out a pathway for firms to quickly recover from the performance decline in the context of the COVID-19 pandemic and other sudden major crisis in the current academic circles. Based on event system theory and structural adjustment to regain fit model, this paper empirically explores the impact of the COVID-19 pandemic on SMEs performance decline and discusses the management innovation response and organizational resilience mechanism of firms by virtue of the questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…More recently, in the context of the COVID-19 pandemic, enterprises faced a drop in performance. One group of authors [40] showed that the pandemic significantly influenced the decline in SMEs' performance and also pointed out the role played by management innovation and organizational resilience in reducing this decline, simultaneously seeing them as a solution for the future when SMEs may be confronted suddenly with significant crises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, in the context of the COVID-19 pandemic, enterprises faced a drop in performance. One group of authors [40] showed that the pandemic significantly influenced the decline in SMEs' performance and also pointed out the role played by management innovation and organizational resilience in reducing this decline, simultaneously seeing them as a solution for the future when SMEs may be confronted suddenly with significant crises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic crisis has prompted a shift in innovation efforts from a relatively stagnant state to one characterized by agility and adaptability (Li et al, 2022). The exponential power of convergence is evident amidst the COVID-19 crisis, as both individuals and organizations display exceptional creativity in devising novel solutions.…”
Section: Innovation and Pandemicmentioning
confidence: 99%
“…Remarkable collaborations between public and private entities have been established in the across the world to address the pandemic. The pandemic crisis has prompted a shift in innovation efforts from a relatively stagnant state to one characterized by agility and adaptability (Li et al, 2022).…”
Section: Innovation and Pandemicmentioning
confidence: 99%
“…When entrepreneurs think that these measures entails to be necessarily and quickly implemented, TP may be exacerbated ( Tomaka et al, 1997 ). The COVID-19 pandemic also causes entrepreneurs unable to start businesses, resulting in lower sales and low profits ( Li et al, 2022 ), which causes economic stress and TP . The criticality of the COVID-19 pandemic is a reflection of the extent to which it affects the long-term development of entrepreneurs and it threatens the achievement of their goals.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Performance is critical to a company’s long-term development, yet owing that EFs are still very young, they often have little revenue, operating deficits, and low chances of survival ( Damodaran, 2009 ), tending to face more uncertainty. The COVID-19 pandemic has a tremendous, irregular, and sudden external impact on EFs and their operations ( Liu et al, 2021 ), which leads to a drastic decline in sales, profits, and market share, finally resulting in a performance decline ( Li et al, 2022 ). Different EFs are somewhat differently affected by the COVID-19 pandemic, so the expected firm performance decline of their entrepreneurs will be different, and the COVID-19 pandemic on their performance pressure ( PP ) will be different.…”
Section: Introductionmentioning
confidence: 99%